CHALLENGES IN SOCIAL ADVOCACY STRATEGIES TO SAFEGUARD THE WELL-BEING OF OLDER ADULTS - Faizal Lim, Siti Munirah; Abu Bakar Ah, Siti Hajar; Abd Wahab, Haris (The Malaysian Journal of Social Administration, 2022)
Population ageing is a remarkable demographic trend that has been escalating in the 21st century. The substantial increase in the aged has significantly impacted the economy and social structure of society. Consequently, the welfare of the older population became the main agenda for every country in the world. Reaching out to older adults and overcoming marginalisation requires an integrated approach through social advocacy strategies. Social advocacy acts as a variable agent in enforcing legislation through social policies and introducing a practical approach to investing in public education regarding ageing. It is essential to address advocacy barriers, promote the cooperation efforts from the state, and seek involvement from the community in rectifying any injustices towards the older adults. Looking at the scenario in Malaysia, the ageing population poses several challenges for the governments and society, which requires urgent responses and timely anticipation from multi-stakeholders in preparing for the future. The importance of social advocacy strategies was highlighted in the Kuala Lumpur Declaration on Ageing (2015) through public awareness campaigns on the wellbeing of older adults, challenges, strengthening the capacity of civil society organisations, and encouraging the participation of older adults in dialogues sessions with the government. Social advocacy has been widely used to change the social context, which includes protecting the rights of older adults. Therefore, this study focuses on the challenges of social advocacy strategies faced by civil society organisations in protecting the interests of older adults in Malaysia.